2015
DOI: 10.3389/fnins.2015.00080
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic bile acids protect human blood-brain barrier endothelial cells from disruption by unconjugated bilirubin: an in vitro study

Abstract: Ursodeoxycholic acid and its main conjugate glycoursodeoxycholic acid are bile acids with neuroprotective properties. Our previous studies demonstrated their anti-apoptotic, anti-inflammatory, and antioxidant properties in neural cells exposed to elevated levels of unconjugated bilirubin (UCB) as in severe jaundice. In a simplified model of the blood-brain barrier, formed by confluent monolayers of a cell line of human brain microvascular endothelial cells, UCB has shown to induce caspase-3 activation and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 87 publications
2
41
0
1
Order By: Relevance
“…Previous studies have reported that hydrophobic bile acids contribute to the breakdown of the blood brain barrier seen during cholestasis via the disruption of tight junctions [28,29]. Alteration of tight junction structure was also observed in cells exposed to toxic bile acids [30,31].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have reported that hydrophobic bile acids contribute to the breakdown of the blood brain barrier seen during cholestasis via the disruption of tight junctions [28,29]. Alteration of tight junction structure was also observed in cells exposed to toxic bile acids [30,31].…”
Section: Discussionmentioning
confidence: 91%
“…UDCA prevents mitochondrial perturbation and consequential mitochondrial swelling [69,86], which are ultrastructural changes commonly observed in cells exposed to toxic bile acids [87][88][89]. Another advantage of UDCA is its ability to cross the blood barrier and prevent changes in its integrity [29].…”
Section: Discussionmentioning
confidence: 99%
“…There are reports that both unconjugated and conjugated bile acids can cross the BBB (Keene et al, 2001 ; Palmela et al, 2015 ; McMillin et al, 2016 ; Figure 3A ), however, the involved mechanisms are still uncertain. Unconjugated bile acids might diffuse across the BBB, because CA, CDCA, and deoxycholic acid (DCA) are capable of diffusing across phospholipid bilayers (Kamp and Hamilton, 1993 ) and their brain levels correlate with their serum levels (Higashi et al, 2017 ).…”
Section: Bile Acids and The Blood-brain Barriermentioning
confidence: 98%
“…Consequently, allowing bile acids and other molecules to diffuse into the brain. UDCA and its glycine-conjugated form glyco-ursodeoxycholic acid (GUDCA) exert a protective effect on brain endothelial cells by reducing apoptosis (Palmela et al, 2015 ). In addition, a recent study showed that microglial cells express TGR5 and that binding of taurine-conjugated UDCA (TUDCA) to TGR5 has anti-inflammatory effects in a mouse model of acute brain inflammation (Yanguas-Casás et al, 2017 ).…”
Section: Bile Acids and The Blood-brain Barriermentioning
confidence: 99%
“…Apart from liver, UDCA is also reported to have anti-apoptotic effect in other cells such as, cholangiocytes [93], brain [94], eyes [95] pro-inflammatory cytokines compared to non-alcoholic drinker of cirrhotic patients who have high level of unconjugated UDCA [5]. A clinical trial conducted on cystic fibrosis patients reported that UDCA protects patients' liver and improves liver function test without affecting their lung function [98].…”
Section: Mechanism Of Action By Udcamentioning
confidence: 99%